Guru Nanak is not at the White House: An essay on the idea of Sikh-American redemption. (3rd July 2017) - Judge, Rajbir Singh; Brar, Jasdeep Singh
ABSTRACT: This article examines the rights-based discourse deployed by Sikh advocacy organizations, the Sikh Coalition and Sikh American Legal Defense & Education Fund, in order to carve an inclusive space within the United States. We interrogate the deep violence of forgetting embedded within this politics that not only sanctions American values and their regulatory might globally, but also integrates the foundational anti-blackness of Western subjectivity into the conceptual structure of Sikhism. Reconsidering these attachments to the American political project and the white-settler state, we argue Sikh organizations fasten Sikhs to ways of life that are inimical to their own flourishing.